2016
DOI: 10.1002/ejlt.201600016
|View full text |Cite
|
Sign up to set email alerts
|

Changes in fatty acid profile and chemical composition of meagre (Argyrosomus regius) fed with different lipid and selenium levels

Abstract: This study aimed to evaluate changes in body composition, specially muscle and liver fatty acid profile in meagre (Argyrosomus regius) fed with different dietary lipid sources and levels, with or without selenium supplementation. Six hundred meagre were fed twice a day, 6 days per week, with eight experimental diets for 60 days. Diets were a combination of fish oil or a vegetable blend (45% linseed + 35% rapeseed + 20% soybean oil), at 12 or 17% of oil and 0 or 1 mg/kg of organic selenium, in a 2 × 2 × 2 facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…This indicates that there were no changes in the chemical composition of the roots, but that their contents were influenced by treatment with Pb and Se. This finding is consistent with results from recent reports on grape pomace [36] and meager [37]. The absorption peaks displacement of certain functional groups involved in heavy metal adsorption changes to different degrees, e.g., the absorption peak of OH group (3,416-3,900 cm −1 ), and carbonyl group (1,000-1,100 cm −1 , and 1,270 cm −1 ), which may act as Pb ligands and participate in the processes of Pb sequestration in coleus roots with exogenous Se treatments [38].…”
Section: D-ftir Spectra Changes Analysissupporting
confidence: 94%
“…This indicates that there were no changes in the chemical composition of the roots, but that their contents were influenced by treatment with Pb and Se. This finding is consistent with results from recent reports on grape pomace [36] and meager [37]. The absorption peaks displacement of certain functional groups involved in heavy metal adsorption changes to different degrees, e.g., the absorption peak of OH group (3,416-3,900 cm −1 ), and carbonyl group (1,000-1,100 cm −1 , and 1,270 cm −1 ), which may act as Pb ligands and participate in the processes of Pb sequestration in coleus roots with exogenous Se treatments [38].…”
Section: D-ftir Spectra Changes Analysissupporting
confidence: 94%
“…Similar results were obtained by Atalay and Bilal [4] who evaluated different commercial diets in sea bream (Sparus aurata) and sea bass (Dicentrarchus labrax). In addition, Yildiz et al (2008) studying with the sea bream and sea bass, Grigorakis et al [18] and Simões et al [19]studying with meagre reported that the fatty acid composition of fish fillet generally reflects the dietary fatty acids. Most probably, these changes reflect variations in the feeding regime applied during culture.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, deleterious effects were observed when high Omega-3 levels were included in diets accompanied by a low level of antioxidants in larval stages of other species such as in sea bass [185] or sparus aurata [19]. This is due to the fact that cartilage and bone cells or matrix vesicles are composed of PUFAs that are very prone to suffer lipid peroxidation, and this can represent a risk for bone health [73,186,187]. These results could be in agreement with our results, due to the diet with a moderate level of Omega-3 seeming to present a higher capacity to combat oxidative stress due to the higher expression of antioxidant molecules and reduced expression of molecules that promote fatty acid oxidation.…”
Section: Molecules That Impact Crucial Cellular Processesmentioning
confidence: 99%